Analisis Manajemen Risiko Pada Proyek Pembangunan dan Penjualan Apartemen - Nanda Ayu Yuliani; Dailibas Dailibas (Jurnal Ilmiah Wahana Pendidikan, 2022)
Apartment development is one solution to the problem of limited residential land that is increasing, especially in some large cities have land limitation problems. The purpose of this study is to identify the risks that may occur in the construction and sale of apartment projects. The amount of risk that occurs is caused by companies that are not careful in analyzing aspects of risk that occur if the project is developed citing internal factors to external factors. Furthermore, this study analyzes the development of the project to avoid risks that may occur, ranging from the development of project development to sales. In the sale of this apartment is done using SWOT analysis that is useful to find out the strengths, weaknesses, threats, and opportunities of apartment sales. Then the results obtained can be continued well. According to the strength and opportunity of the strategic location of apartment development in sales, more marketing strategies that will achieve sales targets.